Real-Time PCR Assays for the Quantification of HCV RNA: Concordance, Discrepancies and Implications for Response Guided Therapy - Strassl, Robert (PLoS One, 2015)
BACKGROUND AND AIMS: Monitoring of chronic Hepatitis C (CHC) treatment relies on HCV RNA quantification by means of real-time PCR methods. Assay specific analytical sensitivities may impact therapy management. METHODS: Comparative analysis between three commercial assays (Roche COBAS AmpliPrep/COBAS TaqMan Version 1 (CAP/CTM Ver. 1), Version 2 (CAP/CTM Ver. 2) and the Abbott RealTime HCV (ART) assay) was performed on 247 available samples taken at key decision time points during antiviral therapy of 105 genotype 1 patients (triple therapy: n = 70; dual therapy: n = 35). RESULTS: Overall concordance of HCV RNA measurements was high between the two Roche systems (89%; n = 220/247) but lower between the Roche assays and the ART (CAP/CTM Ver. 1 vs ART: 77.3%; n = 191/247 and CAP/CTM v.2 vs ART: 80.1%; n = 198/247). Most discrepancies were noted in week 4/8 samples with residual viremia (<LLOQ) detected by ART (<LLOQ: n = 45, 44.1%) but undetectable HCV RNA by CAP/CTM Ver. 1 (<LLOQ: n = 18, 17.6%) or CAP/CTM Ver. 2 (<LLOQ: n = 26, 25.5%). Based on results by CAP/CTM Ver. 1, 13 eligible patients underwent an abbreviated course of therapy (24 weeks). Only 1 patient experienced virologic breakthrough. If tested by ART, only 6/13 patients (46.2%) would have been eligible for shortened treatment. Consequently, RGT guidelines were adapted and shortening of therapy was allowed if residual viremia was detected by ART at week 4/8. CONCLUSION: An abbreviated course of treatment can safely be applied in patients with residual viremia (<LLOQ) detected by ART in samples collected at week 4/8 of treatment.